“Enlightenment Is a Shared Enterprise”: Tree Ecosystems and the Legacy of Modernity in Richard Powers’s The Overstory - Ostalska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2022)
In Richard Powers’s Pulitzer Prize-winning The Overstory (2018) the theme of the novel is the forest ecosystem, with a special emphasis placed on trees, upon whose developmental model the processes of (organic and industrial) growth are scrutinized in this novel. This article examines tree-human assemblages in detail to see how they exchange their material agency and how they relate to the e/Enlightenment project. The essay also explores Powers’s novel to examine how Buddhist values of spiritual enlightenment are contextualized within European Enlightenment and how decentred humanity finds its place among other non-human beings. Apart from fictitious characters from The Overstory, the article draws upon the research of real-life scientists who inspired the creation of Powers’s protagonists: Prof. Simard and Dr. Beresford-Kroeger, along with the work of anthropologist Anna Tsing. In addition, eco-solutions concerning the tree ecosystem (i.e. bio-planning and the seed banks) coming from the scientific field and the field of literature (Powers) are examined to see if today’s progressive ideas can function in the world of the—still, to a large extent, “regressive”—structures of modernity’s legacy. I conclude by arguing that the novel shows that the Enlightenment project is not compatible with the well-being and long-term survival of both humans and non-human beings.